Clot Lysis in a Perfusion System - Bouvier, C. A; Gruendlinger, J; Berthoud, S (Thrombosis and Haemostasis, 1966)
Most information on clot lysis is derived from in vitro methods whereby various components of the clotting and fibrinolytic systems are mixed before an actual clot is formed. This situation bears little relationship to thrombolysis in vivo. Therefore several techniques have been recently proposed, in which pre-formed clots are exposed to the effects of active agents by contact and diffusion rather than by intimate mixing prior to clotting. We describe an apparatus whereby a perfusion is delivered at controlled rates to clots of standard size and volume formed in calibrated tubes. The composition of the clots can be varied as well as the rate of perfusion and the content of perfusate. The surface of contact between the fluid and the fibrin gel is kept constant throughout and the clot-perfusate relationship is as close as possible to the in vivo situation during thrombolytic therapy. Under these conditions clot lysis by Streptokinase appears as a linear function of time, and the rate of lysis is directly related to kinase concentration. Since the clot intrinsic plasminogen-proactivator content is sufficient to ensure lysis, the lysis time finally depends upon the rate of diffusion of the kinase into the gel. Inhibition obtained with various amounts of E-aminocaproic acid incorporated to the clots or added to the perfusion fluid also suggests that diffusion problems are of major importance in physiological and therapeutic thrombolysis.